Application of the POE learning model assisted with the instagram application in improving critical thinking skills - Faridloh, Faridloh; Muspiroh, Novianti; Ubaidillah, Mujib (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This study aims to analyze the improvement of critical thinking skills of grade X students which is applied using the POE (Predict, Observe, Explain) learning model assisted by the Instagram application on environmental change material. The research was carried out at SMAN 1 Susukan using an experimental method with a research design in the form of a pretest-posttest control group design. Sampling using a simple random sampling technique with a sample size of 64 students. The data collection technique was in the form of a reasoned multiple-choice test with a total of 30 questions used to analyze students' critical thinking skills. The data analysis technique consisted of the N-Gain test and statistical tests in the form of normality test, homogeneity test, and hypothesis testing. The results showed that the results of the N-Gain in the experimental class and control class were included in the medium category with values of 0.57 and 0.43. The highest N-Gain value in the experimental class and control class is found in the KBK 2 indicator (analysis) of 0.68 and 0.42 The lowest N-Gain value is found in the KBK 4 indicator (inference) of 0.41 and 0.33. The application of the Instagram-assisted POE learning model can improve critical thinking skills.